2017
DOI: 10.1007/s11356-017-9116-0
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum-modified bentonite: potential for efficient removal of phosphates from fishpond effluents

Abstract: Adsorption has been suggested as an effective method for removing phosphates from agricultural wastewater effluents that contain relatively high phosphate concentrations. The present study focused on the use of a bentonite-lanthanum clay (Phoslock) for reducing the dissolved phosphate concentration in fishpond effluents. Batch experiments with synthetic phosphate-spiked solutions and with fishpond effluents were performed in order to determine adsorption equilibrium isotherms and kinetics as well as to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This would increase relative availability and increase the degradation rate of methomyl under higher pH values. In an aquaculture system, the pH of water is re duced by the CO 2 emitted by aquatic animals such as fish and the acid produced by nitrifica- tion reactions, and a low pH will have a very adverse effect on fish growth (Sipaúbatavares et al 2016, Kurzbaum et al 2017. Therefore, pH plays an important role in maintaining the stable operation of fishpond systems.…”
Section: Phmentioning
confidence: 99%
“…This would increase relative availability and increase the degradation rate of methomyl under higher pH values. In an aquaculture system, the pH of water is re duced by the CO 2 emitted by aquatic animals such as fish and the acid produced by nitrifica- tion reactions, and a low pH will have a very adverse effect on fish growth (Sipaúbatavares et al 2016, Kurzbaum et al 2017. Therefore, pH plays an important role in maintaining the stable operation of fishpond systems.…”
Section: Phmentioning
confidence: 99%
“…Phoslock ® and Al/Ben increased sediment stability by 265% and 101%, respectively, while Al did not stabilize the sediments Dithmer et al (2016). used LMB to conduct a joint field and laboratory-scale study on 10 European lakes from 2006 to 2013, which showed that the P release in sediments was effectively controlled within 2 to 9 years after treatment Kurzbaum et al (2017). used Phoslock ® to treat phosphate wastewater in fish ponds and achieved a removal rate of 94% within 150 min.…”
mentioning
confidence: 99%